An assessment of imperiled habitat in Colorado - Theobald, David, author; Hobbs, Tom, author; Schrupp, Don, author; O'Brien, Lee, author; Natural Resource Ecology Laboratory, Colorado State University, publisher (Colorado State University. Libraries, 1998)
Wildlife habitat is threatened by rapid conversion of agricultural to residential land use throughout the Rocky Mountain West. As a result of these changes, citizens, planners and decision makers need to identify areas of land that offer the greatest risk of harm from encroaching development. We combine statewide maps of historical, current, and projected development patterns with maps of habitat quality to set priorities for habitat protection. We use land cover data from the Colorado Gap Analysis project to develop modeled habitat and indices of species richness and patch value. Patch quality is estimated on the number of sensitive species that could potentially inhabit the patch, the size of the patch, and the relative contribution of the patch to al suitable habitat available to the species. Development (housing density) patterns are derived from US Census Bureau block-group and block-level data. Our analyses reveal that mid-elevation habitat types in mountain valleys as well as riparian and foothills areas on the Front Range are high priorities for conservation.
Keywords: Colorado -- Population; Cities and towns -- Colorado -- Growth; Habitat (Ecology) -- Colorado; Habitat conservation -- Colorado